1999
DOI: 10.1038/sj.cdd.4400455
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in cell death and cell cycle progression in the UV-irradiated epidermis of bcl-2-deficient mice

Abstract: The effect of bcl-2 gene ablation on epidermal cell death induced by UV-B irradiation was investigated in mice. Exposure of depilated back skin of bcl-2 7/7 mice to 0.5 J/ cm 2 UV-B caused a prolonged increase in the number of epidermal cells showing nuclear DNA fragmentation compared to wild-type littermates. Consistently, skin explants from bcl-2-deficient mice exhibited a higher number of sunburn cells per cm epidermis (16.6+2.1 vs 7.0+1.5) following exposure to 0.1 J/cm 2 UV-B in vitro. Furthermore, UV irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 19 publications
(27 reference statements)
2
19
0
2
Order By: Relevance
“…The ability of Akt promoting cell survival is generally known to be based on its ability to phosphorylate on residues necessary for their inactivation of several proapoptotic proteins, including Bad, caspase-9, transcription factors of the forkhead family and IKK. [9][10][11][12] We here presented that Bcl-2 overexpression sustained Akt level and its phosphorylation. Although the increase of antiapoptotic effect of Akt was previously demonstrated in Bcl-2 overexpressing cells, any evidence showing direct association between Bcl-2 overexpression and PI3K/Akt signaling pathway has not been elucidated to date.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The ability of Akt promoting cell survival is generally known to be based on its ability to phosphorylate on residues necessary for their inactivation of several proapoptotic proteins, including Bad, caspase-9, transcription factors of the forkhead family and IKK. [9][10][11][12] We here presented that Bcl-2 overexpression sustained Akt level and its phosphorylation. Although the increase of antiapoptotic effect of Akt was previously demonstrated in Bcl-2 overexpressing cells, any evidence showing direct association between Bcl-2 overexpression and PI3K/Akt signaling pathway has not been elucidated to date.…”
Section: Discussionmentioning
confidence: 85%
“…Overexpression of either of these proteins serves to protect cells against apoptosis induced by such diverse stimuli as viral infection, hypoxia, ionizing radiation or chemotherapeutic agents. [7][8][9][10][11] In vivo and in vitro studies have shown that Bcl-2 regulates intracellular Ca 2+ levels and prevents the loss of mitochondrial membrane potential induced by proapoptotic stimuli. 12 It has been suggested that Bcl-2 may act as an ion channel and regulates the release of cytochrome c from mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, galectin-7 operates in vivo as a fine tuner, ensuring the completion of a robust and short apoptotic reaction in response to UVB stress. It is worth noting that this information could only have been obtained by examining the kinetics of the apoptotic response over the (Ziegler et al, 1994;Gillardon et al, 1999;Grossman et al, 2001), would have been misleading. For example, at 12 h post-UVB, the reduced number of apoptotic cells in the mutant mice could have been taken as a proof of a proapoptotic role, whereas the opposite conclusion could have been drawn from the results obtained at 9 h post-UVB.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 Indeed, the effects of both donor T cells and UV irradiation are pleiotropic. UV irradiation causes acute cell death and local inflammation, [49][50][51][52] and alloreactive T cells induce systemic cytokines and local inflammation in skin and can directly target nonhematopoietic and hematopoietic cells in addition to LCs. Our finding that donor LCs engrafted in Langerin-DTA recipients, which have a very specific loss of only LCs, 23 without the need for allogeneic T cells or UV irradiation indicates that skin inflammation per se is not required for donor LC engraftment.…”
Section: Discussionmentioning
confidence: 99%